Sistem Monitoring Kebocoran Gas SF6 Pada Sistem GIS menggunakan Modul LoRa Berbasis IoT - Kealvin Al Akbary, Muhammad (Jurnal Teknik Ilmu dan Aplikasi, 2023)
The research introduces a Gas Insulating Substation (GIS) Monitoring System for SF6 gas leakage, aiming to mitigate the risk of significant gas leaks. The GIS, comprising three phases (R, S, T), utilizes SF6 gas with protective alarms and leakage indicators on each phase. However, the current practice of sequentially checking leak points among phases poses challenges, such as potential damage to the SF6 gas refill valve, leading to larger leaks. In response, a Monitoring System using LoRa-based IoT modules was developed. The research methodology involved checking electrical flow through voltage sensors and pressure sensors on the nonferrous tubes of the three phases to identify leakage points. The results indicated that the implemented SF6 Gas Leakage Monitoring System using LoRa-based IoT Modules effectively assists High Voltage Substation operators in reducing valve damage caused by mishandling SF6 gas leaks. Operators can monitor leaky tubes through a web interface and receive Telegram notifications, expediting response times. Additionally, the system proves cost-effective, requiring only around 1 million rupiahs compared to the conventional cable installation costing approximately 5 million rupiahs, without necessitating modifications to the existing Substation system.